2023
DOI: 10.1136/bmjmed-2023-000664
|View full text |Cite
|
Sign up to set email alerts
|

Diet in the management of type 2 diabetes: umbrella review of systematic reviews with meta-analyses of randomised controlled trials

Edyta Szczerba,
Janett Barbaresko,
Tim Schiemann
et al.

Abstract: ObjectiveTo systematically summarise and evaluate the existing evidence on the effect of diet on the management of type 2 diabetes and prevention of complications.DesignUmbrella review of systematic reviews with meta-analyses of randomised controlled trials.Data sourcesPubMed, Embase, Epistemonikos, and Cochrane, from inception up to 5 June 2022.Eligibility criteria for selecting studiesSystematic reviews with meta-analyses of randomised controlled trials reporting summary effect estimates on the effect of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Large body of evidence indicates that a MedDiet offers many benefits to patients with type 2 diabetes (T2D), both in the prevention of the disease and in its management such as in glycemic control [ 35 37 ]. This statement is based on epidemiological studies and on the results of a randomized controlled trial.…”
Section: Diabetes Riskmentioning
confidence: 99%
“…Large body of evidence indicates that a MedDiet offers many benefits to patients with type 2 diabetes (T2D), both in the prevention of the disease and in its management such as in glycemic control [ 35 37 ]. This statement is based on epidemiological studies and on the results of a randomized controlled trial.…”
Section: Diabetes Riskmentioning
confidence: 99%
“…These complex interactions are crucial for regulating gene transcription, modulating the structure and function of cellular membranes, influencing ion channel activities and electrophysiological processes, and affecting a myriad of biological pathways, as elucidated by Wu et al 44 The growing body of scientific literature emphasizes the critical role of diet quality as a fundamental determinant shaping the longterm impacts of dietary practices on the incidence and management of obesity and T2D. [45][46][47] Within the scope of obesity, a robust scientific consensus exists on the benefits of consuming a diet abundant in minimally processed, bioactive foods. This dietary pattern encompasses diverse fruits, non-starchy vegetables, whole grains, nuts, seeds, legumes, oils extracted from plants, yogurt, and fish-all noted for their nutrient density and health-promoting properties.…”
Section: Nutritionmentioning
confidence: 99%
“…Contemporary management of obesity and T2D now incorporates dietary pattern-based interventions. Systematic reviews have provided evidence supporting the efficacy of dietary patterns such as the Mediterranean diet, 47,55 the Dietary Approaches to Stop Hypertension (DASH) diet, 56 low-carbohydrate diets, 57 the ketogenic diet, 58 and plant-based diets 59 in reducing the prevalence of obesity and T2D. These diets emphasize the consumption of fruits, vegetables, whole grains, lean proteins, and healthy fats, while minimizing processed foods and added sugars.…”
Section: Nutritionmentioning
confidence: 99%
“…There is growing evidence leading to recommendations from numerous scientific medical societies of diabetology on the use of these dietary approaches to intervene against type 2 diabetes [ 16 , 17 , 18 ] and overall protection against cardiovascular diseases [ 19 ]. However, contemporary literature reviews assessing the comparative effects of carbohydrate restricted diets versus low-fat control diets in overweight/obese patients with type 2 diabetes mellitus have shown divergent and inconclusive results regarding the impact on glycated hemoglobin, weight loss, and cardiovascular risk factors [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Dietary fats, particularly saturated fatty acids (SFAs), have been implicated as the cause of the significant rise in obesity and its related diseases [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, contemporary literature reviews assessing the comparative effects of carbohydrate restricted diets versus low-fat control diets in overweight/obese patients with type 2 diabetes mellitus have shown divergent and inconclusive results regarding the impact on glycated hemoglobin, weight loss, and cardiovascular risk factors [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Dietary fats, particularly saturated fatty acids (SFAs), have been implicated as the cause of the significant rise in obesity and its related diseases [ 24 ]. On the contrary, several systematic reviews challenge the link between total SFA intake with cardiovascular disease and recent studies showed that short-chain saturated fatty acids (SCSFAs) especially from dairy foods [ 27 , 28 , 29 , 30 ] may exert potential beneficial effects both on metabolic and mental health outcomes [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%